THE EFFECT OF THE LADDER DRILL-BASED METHOD ON THE ABILITY TO DRIBBLE FOOTBALL PLAYERS - Akhmad Sobarna; Sumbara Hambali; Kurnia Sandi; Supriadi, Idris; Henry Asmara (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2023)
The purpose of this study was to determine the effect of the ladder drill-based method on the ability to dribble football players. The method used in this study was the experimental method, design